Study guides

☆☆

Q: 4x plus 2 - 6x -1?

Write your answer...

Submit

Still have questions?

Related questions

- 4X - 6X + 2 = 2(- 2X - 3X + 1) -------------------------that is all the factoring I can see to do here

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

6x + 3 = 2x + 5 4x = 2 x=1/2

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2

If: 1-2x-5 = 4x+2 Then: -2x-4x = 2-1+5 And: -6x = 6 So: x = -1

8x^2 + 6x - 5 = 8x^2 + 10x - 4x - 5 = 2x * (4x + 5) - (4x + 5) = (2x -1) * (4x + 5)

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

2 - 4x - 2x + 4 = 6 - 6x

4x-6x = -2

4x(4x^2 - 6x + 7)

the solution for the inequality 4x + 2 - 6x < -1 was x < 3/2

People also asked

Featured Questions